2012
DOI: 10.1007/s10995-012-1094-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Maternal Food Security a Predictor of Food and Drink Intake Among Toddlers in Oregon?

Abstract: Food insecurity has detrimental effects on the mental, physical, and behavioral health of developing children. Few studies, however, have sought to determine whether associations exist between food insecurity and intake of vegetables, fresh or canned fruit, candy or cookies, French fries, fast food, water, milk, fruit juices, fruit drinks, soda, and sports drinks. To identify independent associations that exist between maternal food insecurity and food and drink intake among toddlers, population-based data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
(37 reference statements)
5
18
0
2
Order By: Relevance
“…(yes/no). This standard question is one of the items included in the U.S. Department of Agriculture's (USDA) abbreviated 6-item food security module [32] and has been used elsewhere [33,34]. Responses were dichotomized to food insecure (yes) and food secure (no).…”
Section: Study Variablesmentioning
confidence: 99%
“…(yes/no). This standard question is one of the items included in the U.S. Department of Agriculture's (USDA) abbreviated 6-item food security module [32] and has been used elsewhere [33,34]. Responses were dichotomized to food insecure (yes) and food secure (no).…”
Section: Study Variablesmentioning
confidence: 99%
“…In a study of 1,522 mother-toddler pairs, Cunningham et al found that maternal food insecurity was associated with a lower weekly intake of fruits and vegetables and a higher weekly intake of soda for toddlers. [64] Nguyen et al found that food insecurity was adversely associated with maternal diet diversity among mothers with children 2 years old or younger. [65] No association was found for child diet diversity.…”
Section: Special Considerations: Pregnancy Infants and Toddlersmentioning
confidence: 99%
“…Although infant feeding practices are one of the most important determinants of the health of young children, there are limited data on the relationship between HHFI and breastfeeding [20-22] and complementary feeding practices [19-21, 23]. Further, we are unaware of any studies evaluating the association between HHFI and infant feeding in the context of HIV.…”
Section: Introductionmentioning
confidence: 99%